Failure on the Foam Eyes Closed Test of Standing Balance Associated With Reduced Semicircular Canal Function in Healthy Older Adults. Issue 2 (March 2019) - Anson, Eric; Bigelow, Robin T.; Studenski, Stephanie; Deshpande, Nandini; Agrawal, Yuri
Abstract : Objectives: Standing on foam with eyes closed (FOEC) has been characterized as a measure of vestibular function; however, the relative contribution of vestibular function and proprioceptive function to the FOEC test has not been well described. In this study, the authors investigate the relationship between peripheral sensory systems (vestibular and proprioception) and performance on the FOEC test in a cohort of healthy adults. Design: A total of 563 community-dwelling healthy adults (mean age, 72.7 [SD, 12.6] years; range, 27 to 93 years) participating in the Baltimore Longitudinal Study of Aging were tested. Proprioceptive threshold (PROP) was evaluated with passive motion detection at the right ankle. Vestibulo-ocular reflex (VOR) gain was measured using video head impulses. Otolith function was measured with cervical and ocular vestibular-evoked myogenic potentials. Participants stood on FOEC for 40 sec while wearing BalanSens (BioSensics, LLC, Watertown, MA) to quantify center of mass sway area. A mixed-model multiple logistic regression was used to examine the odds of passing the FOEC test based on PROP, VOR, cervical vestibular-evoked myogenic potential, and ocular vestibular-evoked myogenic potential function in a multisensory model while controlling for age and gender. Results: The odds of passing the FOEC test decreased by 15% ( p < 0.001) for each year of increasing age and by 8% with every 0.1 reduction in VOR gain ( p = 0.025). Neither PROP nor otolith function was significantly associated with passing the FOEC test. Conclusions: Failure to maintain balance during FOEC may serve as a proxy for rotational vestibular contributions to postural control. Semicircular canals are more sensitive to low-frequency motion than otoliths that may explain these relationships because standing sway is dominated by lower frequencies. Lower VOR gain and increased age independently decreased the odds of passing the test.